Violence, therapeutic bond and perversion - Rojas, Hugo (Revista de Psicología, 1999)
First, some generalities. In the reflection about violence, placed on this table where, on the one hand, it is exposed as if from a telescope, looking from afar and amplifying; I have the microscope. Because going from the more general problems of violence and civilization, to violence in culture, to the problem of presence, of violence in the therapeutic bond, as far as I am concerned, in the analytical setting, is to go to microscopic problems. Which is not to say that these problems are insignificant.